PENGARUH PROFITABILITAS, FREE CASH FLOW DAN INVESTMEN OPPORTUNITY SET TERHADAP KEBIJAKAN UTANG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014 - Eka Purwanti, 12.05.52.0196; Susilowati, Yeye (Students Journal of Accounting and Banking, 2016)
This study aimed to determine the effect Profitability, Free Cash Flow (FCF), Investment Opportunity Set (IOS) to the Debt Policy. The population in this study is a manufacturing company listing on the Indonesian Stock Exchange (BEI) in 2010-2014. This research was conducted by using quantitative data. The research sample was determined by purposive sampling techniques and sample menghasillan 95 companies for analysis. This quantitative analysis includes the classical assumption (normality test, multicollinearity, heteroscedasticity test, autocorrelation test), multiple linear regression test, test the feasibility of this model through the F test, the coefficient of determination. and t test. T test results showed that the only variable partial IOS significant negative effect on the variable Debt Policy, while the variable profitability, Free Cash Flow does not affect the Debt Policy. Simultaneously profitability, FCF, IOS has a significant effect on the Debt Policy. While the coefficient of determination through the adjusted R-square showed 8.7% means that the Debt Policy variable variation can be explained by the variable profitability, FCF, IOS, while the remaining 90.8% is explained by other causes beyond the model.Keywords: Profitability, FCF, IOS, Debt Policy